PLATE-Seq for genome-wide regulatory network analysis of high-throughput screens - Erin C. Bush (Nature Portfolio, 2017)
Despite the importance of pharmacological and functional genomic screens the readouts are of low complexity. Here the authors introduce PLATE-Seq, a low-cost genome-wide mRNA profiling method to complement high-throughput screening.